Realismo e idealismo na política internacional de Joaquim Nabuco - Chacon, Vamireh (Ciência & Trópico, 2011)
RESUMOAnalisa a trajetória política de Joaquim Nabuco, mostrando como conviveram no eminente homem público o realismo e o idealismo político diante das demandas da política internacional brasileira no início do século XX. Conclui que o cosmopolitismo nabuquiano também confraternizava com o seu lado patriótico e regionalista, apontando-o como figura de estadista complementar àquela do Barão do Rio Branco, seu principal companheiro de jornada.ABSTRACTRealism and Idealism in Joaquim Nabuco’s International Policy. v. 29, n. 2, p. 397-404, jul./dez. 2001.The essay analyses Joaquim Nabuco’s political trajectory, showing the way political realism and idealism were both present in his intellectual personality in facing the Brazilian international political demands in the beginnings of the 1920s. The essay concludes that Nabuco’s cosmopolitism was harmonious in relation to his patriotic and regionalist ideas, calling attention to the fact that he was a complemantary figure as a statesman in relation to that of the Baron of Rio Branco, his main fellow in his diplomatic career.RÉSUMÉRéalisme et Idéalisme dans la Politique Internationale de Joaquim Nabuco. v. 29, n. 2, p. 397-404, jul./dez. 2001.L’auteur analyse la trajectoire politique de Joaquim Nabuco, montrant comment cohabitèrent chez cet éminent homme public, le réalisme et l’idéalisme face aux tendances de la politique internationale brésilienne du début du XX è siècle. Il conclut que le cosmopolitisme de Nabuco fraternise avec son côté patriotique et régionaliste, le désignant comme l’homme d’état complémentaire du Baron de Rio Branco, son principal compagnon de route.